Ciprofloxacin-Resistant Salmonella enterica Serovar Kentucky in Canada - Michael R. Mulvey; David A. Boyd; Rita Finley; Ken Fakharuddin; Stacie Langner; Vanessa Allen; Lei Ang; Sadjia Bekal; Sameh El Bailey; David Haldane; Linda Hoang; Greg Horsman; et al. (Emerging Infectious Diseases, 2013)
We report emergence of ciprofloxacin-resistant Salmonella enterica serovar Kentucky in Canada during 2003–2009. All isolates had similar macrorestriction patterns and were multilocus sequence type ST198, which has been observed in Europe and Africa. Ciprofloxacin-resistant S. enterica serovar Kentucky represents 66% of all ciprofloxacin-resistant nontyphoidal Salmonella sp. isolates observed in Canada since 2003.